(3JbjjO Ce JMQjQ ddJLGQI GdOhdjIs - (3ShRj YOdj(B, (3fGTOs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2010)
(3JGQjN GJaGbjI (BTBT (3h GdGNJdGaGJ GdGSGSjI Hjf (BTBT (3Whcjh h(BTBT (3defXeI GdJLGQI GdYGdejI (BWTO (3GdgOa GdQFjSj ef EJaGbjI (BTBTk (3, gjcd GJaGbjI GdYhGFb GdafjI CeGe GdJLGQI , GdBKGQ GdYGeI dGJaGbjI (BWTO (3Ydi GJaGbjI GdYhGFb GdafjI CeGe GdJLGQI , fWGb JWHjb EJaGbjI (BTBT (3, BKGQ EJaGbjI (BTBT (3Ydi JLGQI GdOhd GdfGejI (B.s
(3edGMb U(B.75s
Keywords: (3GdGJaGbjGJ GdJLGQjIs; (3GdJLGQIs; (3GdJLGQI GdNGQLjIs